New Reaction of Iodine with Sterically Hindered Acetylene, 1,2,4,5-Tetramethyl-3,6-bis(phenylethynyl)benzene in Dimethyl Sulfoxide; Russian Journal of Organic Chemistry; Vol. 32, iss. 8 - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Zholobova G. A.; Vasileva V. P.; Habicher W.; Filimonov V. D. Viktor Dmitrievich (1996, 1996)
В фонде НТБ ТПУ отсутствует